Discover a wealth of knowledge at Westonci.ca, where experts provide answers to your most pressing questions. Get detailed answers to your questions from a community of experts dedicated to providing accurate information. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Answer:
- p = -3
- q = 2
- remainder = 4
Step-by-step explanation:
We want to find the constants 'a', 'p', and 'q' such that ...
(x -a)(x -1)(x +2) ≡ x³ +px +q
(x -a)(x² +x -2) ≡ x³ +px +q
x³ +x² -2x -ax² -ax +2a ≡ x³ +px +q
This gives rise to three equations:
1 -a = 0 . . . . coefficient of x²
-2 -a = p . . . coefficient of x
2a = q . . . . . constant
The first of these tells us a=1. Then, p=-3 and q=2.
The values of p and q are -3 and 2, respectively.
__
The remainder from division by (x+1) is the value of the cubic for x=-1. That value is ...
(-1)³ -3(-1) +2 = -1 +3 +2 = 4
The remainder from division by (x+1) is 4.
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.